Association between dietary pattern and metabolic disorders in children and adolescents with urolithiasis - Mariana S. Vieira; Priscila de C. Francisco; Ana Luiza L.C. Hallal; Maria Goretti M.G. Penido; Nilzete L. Bresolin (Elsevier, 2020)
Objective: To describe the dietary patterns and occurrence of metabolic disorders in children and adolescents with urolithiasis treatment at a referral hospital in southern Brazil in order to learn the features of urolithiasis in this population to better develop preventive actions. Methods: Descriptive study conducted between 2016 and 2017 in a tertiary care referral hospital. Fourty patients aged 2-19 years old with urolithiasis proven by imaging were included. Clinical and dietary data were obtained through interviews and medical records. For statistical analyses, the chi-squared test was performed. Results: 40 individuals were analyzed. Mean age at diagnosis was 7.2 ± 4 years. 25% were overweight or obese. 95% had metabolic disorders, hypocitraturia being the predominant type. Protein intake was adequate in all participants and carbohydrate intake, in 70% of them; 37.5% had lipid intake above recommended and 65% had low fiber intake. The mean daily sodium intake was 2.64 g (±1.74), with 55% of participants ingesting more than the recommended amount. A total of 52.5% had low potassium intake, with a mean of 4.79 g/day (±2.49). Calcium intake was adequate in 27.5%. No significant differences were identified in relation to mean daily consumption among participants with or without the various metabolic disorders. Conclusion: Pediatric urolithiasis is often accompanied by metabolic disorders; therefore, metabolic evaluation should be part of the diagnostic process and subsequent analysis of these patients' dietary patterns, helping to optimize treatment and prevent recurrences and complications. Resumo: Objetivo: Descrever o padrão alimentar e ocorrência de distúrbios metabólicos em crianças e adolescentes portadoras de urolitíase acompanhadas em hospital de referências no sul do Brasil a fim de conhecer as particularidades da urolitíase nessa população para melhor desenvolver ações de prevenção. Métodos: Estudo observacional descritivo realizado entre 2016 e 2017 em centro de referência em atenção terciária. Foram selecionados 40 pacientes de 2 a 19 anos com urolitíase comprovada por exame de imagem. Dados clínicos e alimentares foram obtidos através de prontuário e entrevista. Para análise estatística, utilizou-se o teste qui-quadrado. Resultados: Foram analisados 40 indivíduos, 55% masculinos. Idade média ao diagnóstico 7,2±4 anos. 25% tinham sobrepeso ou obesidade. 95% tinham distúrbios metabólicos, predominando a hipocitratúria. O consumo proteico e de carboidratos foi adequado em 100% e 70% dos participantes, respectivamente. 37,5% apresentaram ingestão de lipídeos acima do recomendado e 65% apresentaram ingestão de fibras alimentares abaixo do recomendado. O consumo diário médio de sódio foi de 2,64 g (±1,74), com 55% acima do recomendado. 52,5% apresentaram baixa ingestão de potássio com média de 4,79 g/dia (±2,49). O consumo de cálcio foi adequado em 27,5%. Não foram identificadas diferenças significativas em relação ao consumo médio diário dos nutrientes entre os participantes com ou sem os diversos distúrbios metabólicos. Conclusões: A urolitíase pediátrica é frequentemente acompanhada de distúrbios metabólicos, o que confirma a necessidade de avaliação metabólica adequada ao diagnóstico e análise do padrão alimentar a fim de identificar erros alimentares e otimizar o tratamento destes distúrbios, prevenindo recorrências e complicações.